USING OF UKRVO DATA AND SOFTWARE FOR NEW REDUCTIONS OF PHOTOGRAPHIC OBSERVATIONS OF SELECTED MINOR PLANETS - Protsyuk, Yu.; Maigurova, N.; Prorsyuk, S.; Golovnia, V. (Одеські астрономічні публікації, 2016)
The new reductions of available photographic plates of UkrVO digital archive containing images of selected minor planets were conducted. Data processing of these plates were carried out to check the possibility of obtaining the new positions with high accuracy in the system of Tycho2/UCAC4 reference catalogues. Archives of the Research Institute “Nikolaev Astronomical Observatory” (NAO) and Main Astronomical Observatory ofNationalAcademyof Science (MAO) were used. We have chosen near 60 plates from these archives. Observational epochs of the plates were in the range from 1974 to 1991. Usually, there were 3 exposures in each plate and each plate was scanned 6 times with 1600 dpi resolution. The full identification was conducted and coordinates of all objects were obtained with usage of different options of astrometric reductions. The inner accuracy of obtained positions is within of 0.03″-0.40″. The comparison of the new topocentric positions of minor planets with Horizons ephemeris was made for calculation (O – C) residuals and their RMS. The matching with MPC data is present.